Spatial Age Distribution of Classical Cepheids in Spiral Galaxies: The Cases of M31 and M33 - Giulia De Somma; Marcella Marconi; Vincenzo Ripepi; Santi Cassisi; Roberto Molinaro; Ilaria Musella; Teresa Sicignano; Erasmo Trentin (The Astrophysical Journal Letters)
Classical Cepheids can be used as age indicators due to well-established period–age and period–age–color relations. G. De Somma et al. refined these relations by including a metallicity term and different mass–luminosity assumptions. In this study, we apply the period–age–metallicity relation for the first time to samples of classical Cepheids in M31 and M33. For both galaxies, we consider Cepheid coordinates and spatial distributions, along with the metallicity gradient by D. Zaritsky et al. and L. Magrini et al. to provide a metallicity estimate for each pulsator. Therefore, by applying the period–age–metallicity relation, we derive the individual ages of each Cepheid. By combining the individual ages and spatial distributions of classical Cepheids in M31 and M33, we built detailed age maps for both galaxies. Our analysis confirms a radial age gradient, with younger Cepheids preferentially found toward the galactic center. In M31, we confirm an outer ring at ∼11 kpc, consistent with previous studies, and identify for the first time an inner ring at ∼7 kpc, possibly associated with star formation episodes. Comparing age gradients at different angles, we find a consistent general trend of ages increasing monotonically with radius. At the same time, we observe smaller-scale differences, particularly in the 90°–180° quadrant, suggesting asymmetric star formation and possible dynamical influences. In contrast, M33 displays a steeper global age gradient, indicating a higher concentration of young stars toward its center. This study highlights the utility of Cepheids as stellar population tracers, providing insights into the star formation and dynamical evolution of spiral galaxies. Future works will extend this methodology to additional galaxies.